Laparoscopic Gastric Plication versus Laparoscopic Sleeve Gastrectomy: An Up-to-Date Systematic Review and Meta-Analysis - Konstantinos Perivoliotis; Eleni Sioka; Georgia Katsogridaki; Dimitrios Zacharoulis (Journal of Obesity)
Introduction. A meta-analysis was conducted in order to provide an up-to-date comparison of laparoscopic sleeve gastrectomy (LSG) and laparoscopic gastric plication (LGP) for morbid obesity. Materials and Methods. The PRISMA guidelines and the Cochrane Handbook for Systematic Reviews of Interventions were used for the conduction of this study. A systematic literature search was performed in the electronic databases (MEDLINE, CENTRAL, and Web of Science and Scopus). The fixed effects or random effects model was used according to the Cochran Q test. Results. Totally, 12 eligible studies were extracted. LSG displayed a statistically significant lower rate of overall complications (OR: 0.35; 95% CI: 0.17, 0.68; p=0.002) and a sustainable higher %EWL through all time endpoints (OR: 4.86, p=0.04; OR: 7.57, p<0.00001; and OR: 13.74; p<0.00001). There was no difference between the two techniques in terms of length of hospital stay (p=0.16), operative duration (p=0.81), reoperation rate (p=0.51), and cost (p=0.06). Conclusions. LSG was demonstrated to have a lower overall complications and a higher weight loss rate, when compared to LGP. Further RCTs of a higher methodological quality level, with a larger sample size, are required in order to validate these findings.